Pengaruh Abu Dasar (Bottom Ash) Sebagai Bahan Substitusi Pasir Pada Sebagian Sifat Beton Segar Dan Beton Keras - Afrianda, Yogi; Kurniawandy, Alex; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The research is a continuation of previous research that aims to obtain the characteristic of fresh and hard concrete using bottom ash as substitute material sand on normal concrete. At this stage of research focused on analyzing the bulk density, workability, permeability and sulfate resistance. The percentage of bottom ash waste that is used are 0% and 30% of the weight of the sand. The results show that using 30% of bottom ash decrease the workability and bulk density on concrete. Meanwhile, the use of 30% bottom ash also increase the value of permeability on the concrete. On testing of sulfate resistance, concrete with 0% of bottom ash increases the compressive strength at age of 28 days, then will decrease at the age of 56 days and 90 days. As well as on the concrete with 30 % of bottom ash, the compressive strength decreases at the age of 56 and 90 days.Keywords : bottom ash, bulk density, workability, permeability, sulfate resistance